Migratory pattern and city slums in Lagos State, Nigeria (2021)
The study specifically did a situational analysis of the concept, causes, impact and the effectiveness of Lagos State Government Policies and Programmes on city slums and migratory patterns in Lagos State, with a view to making recommendations that will ameliorate its effects as well as sustain Lagos State. The study employed the qualitative analysis of secondary data related to Lagos State, while primary data were collected through personal interview and direct observation. Various factors ranging from economic, social, safety, environmental to political factors have been discovered to be responsible for the movement of people and resources from one place to another. It is categorized into push and pull factors. In Lagos State, Nigeria, high rent-fee, coastal lines, land-grabbing phenomenon, overpopulation and many other factors are found to be the immediate factors that propelled many people to reside in slums. Government made various efforts to curb the problems, however the problems persist. The study recommended that there is need for Government to build low-cost houses for people thereby digesting slums as well as curbing various nefarious acts by the downtrodden in the society.